Phase Transitions of Sweetened Condensed Milk in Extended Storage Temperature Ranges - Anastasia E. Ryabova; Vladislav A. Tolmachev; Aram G. Galstyan (Техника и технология пищевых производств, 2022)
Sweetened condensed milk is a popular food in various climatic zones, including those regions where average winter temperature falls below –30°C. Such low temperatures can trigger crystallization because they disrupt the native structure of biopolymers. These processes spoil the quality of sweetened condensed milk. However, no scientific publications feature the cryoscopic temperature of sweet condensed milk or systematize the data on its low-temperature storage. Sugar, sugar-milk, and milk solutions of various concentrations were frozen to determine their cryoscopic temperature by the thermographic method using a Testo 176T4 meter (Germany) with K-type probes (NiCr-Ni) at –78.5°C. The phase transitions were studied using a Mettler Toledo DCS 822e DSC analyzer. The nucleation temperature, the cryoscopic temperature, and the subcooling degree depended on the concentration and the type of the solute. For sugar solutions, the cryoscopic temperature varied from –0.4 ± 0.1 to –6.4 ± 0.1°C; for sugar-milk solutions, it ranged from –2.1 ± 0.1 to –10.9 ± 0.1°C; for whole milk solutions, it was from –0.4 ± 0.1 to –4.6 ± 0.1°C. The thermographic method failed to obtain the phase transition and the cryoscopic temperature in analogue models of sweetened condensed milk. The loss of fluidity was about –30°C when the storage time exceeded 2 h. This effect was comparable to 54 min of storage at –35°C. The differential scanning calorimetry meth od showed that the phase transition occurred at –80°C. This research opens new prospects for differential scanning calorimetry studies of phase transitions in condensed sweetened dairy products.